Patterns of Circulating Inflammatory Biomarkers in Older Persons with Varying Levels of Physical Performance: A Partial Least Squares-Discriminant Analysis Approach - Marzetti, Emanuele; Landi, Francesco; Marini, Federico; Cesari, Matteo; Buford, Thomas W.; Manini, Todd M.; Onder, Graziano; Pahor, Marco; Bernabei, Roberto; Leeuwenburgh, Christiaan; Calvani, Riccardo (Frontiers in Medicine, 2014)
Background. Chronic, low–grade inflammation and declining physical function are hallmarks of the aging process. However, previous attempts to correlate individual inflammatory biomarkers with physical performance in older people have produced mixed results. Given the complexity of the inflammatory response, the simultaneous analysis of an array of inflammatory mediators may provide more insights into the relationship between inflammation and age–related physical function decline. This study was designed to explore the association between a panel of inflammatory markers and physical performance in older adults through a multivariate statistical approach. Methods. Community–dwelling older persons were categorized into “normal walkers” (NWs; n = 27) or “slow walkers” (SWs; n = 11) groups using 0.8 m/s as the 4–meter gait speed cutoff. A panel of 14 circulating inflammatory biomarkers was assayed by multiplex analysis. Partial Least Squares–Discriminant Analysis (PLS–DA) was used to identify patterns of inflammatory mediators associated with gait speed categories. Results. The optimal complexity of the PLS–DA model was found to be 5 latent variables. The proportion of correct classification was 88.9% for NW subjects (74.1% in cross–validation) and 90.9% for SW individuals (81.8% in cross–validation). Discriminant cytokines in the model were interleukin 8, myeloperoxidase, tumor necrosis factor alpha (all higher in the SW group), and P–selectin, interferon gamma and granulocyte–macrophage colony–stimulating factor (all higher in the NW group). Conclusions. Distinct profiles of circulating inflammatory biomarkers characterize older subjects with different levels of physical performance. The dissection of these patterns may provide novel insights into the role played by inflammation in the disabling cascade and possible new targets for interventions.